Comparison of In-hospital Outcomes of Percutaneous Coronary Intervention between Young Male and Female Patients with Acute Coronary Syndrome (University Heart Journal, 2018)
Background: Acute coronary syndrome (ACS) among young people is increasingly prevalent. However, there is a scarcity of data on the gender differences of in-hospital adverse outcomes among ACS patients after percutaneous coronary intervention (PCI) among young Bangladeshis. This study was conducted to compare the in-hospital outcomes of PCI between young males and females presenting with ACS.Methods: This prospective observational study was done in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD) fromApril 2016 to March 2017. 190 young patients with ACS and undergoing PCI were enrolled. They were equally divided into two groups, group I (young females